Elaboration of countertransference experience and the workings of the working alliance. - Barreto, João F. (2022)
Alliance may impact psychotherapy outcomes both as a precondition that enables therapeutic work and an evolving process that is therapeutic in itself. This study examined the participation of the elaboration of countertransference experience (ECE) in alliance variation between therapist– client dyads early in therapy and within dyads over time. A total of 44 session assessments nested within 12 dyads were modeled through longitudinal multilevel analyses and utilized to examine the associations between the ECE dimensions of Immersion and Reflection and alliance components across 4 time points within the first 10 sessions of psychotherapy. Results supported the importance of initial ECE to explain differences and examine the participation of ECE in the resolution of alliance ruptures.